2010
DOI: 10.1177/1741143210383896
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Be Leaders in Higher Education: What Helps or Hinders Women’s Advancement as Leaders in Universities

Abstract: This article examines 110 reported incidents from an online survey of 26 women from each of the eight universities in New Zealand. They responded to questions asking them to describe times when work and non-work situations have helped or hindered their advancement in university leadership roles. Five key themes, incorporating a range of factors, emerged as making a difference to advancement as leaders. These themes are: work relationships; university environment; invisible rules; proactivity; and personal circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(118 citation statements)
references
References 15 publications
4
109
2
3
Order By: Relevance
“…Researchers (Arini et al, 2011;Kellerman & Rhodes, 2014;Keohane, 2014;Pyke, 2013;Tessens et al, 2011;Toma`s et al, 2010) have been able to identify actual or perceived barriers and obstacles to female advancement in higher education settings. Such barriers and obstacles are perceived as gender-based and function at social, organizational, and personal levels (Diehl, 2014).…”
Section: Barriers and Obstacles That Hinder Leadership Opportunities mentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers (Arini et al, 2011;Kellerman & Rhodes, 2014;Keohane, 2014;Pyke, 2013;Tessens et al, 2011;Toma`s et al, 2010) have been able to identify actual or perceived barriers and obstacles to female advancement in higher education settings. Such barriers and obstacles are perceived as gender-based and function at social, organizational, and personal levels (Diehl, 2014).…”
Section: Barriers and Obstacles That Hinder Leadership Opportunities mentioning
confidence: 99%
“…In the literature gathered (Arini et al, 2011;Kellerman & Rhodes, 2014;Keohane, 2014;Pyke, 2013;Tessens et al, 2011;Toma`s et al, 2010), difficulty balancing the demands of family and work emerged as a recurrent barrier to female advancement in higher education. For example, Kellerman and Rhodes (2014) highlighted the disproportionate burdens in the home where women attend to family responsibilities more than their spouses.…”
Section: Barriers and Obstacles That Hinder Leadership Opportunities mentioning
confidence: 99%
See 1 more Smart Citation
“…Most researches, by focusing on the mentors and women administrators, disclose that mentorship may be one of the great motivations for career advancement of women (Blum et al, 1994;Brown, 2005;Beck, 2008;Kiamba, 2008;Madson, 2008;Airin, 2010;Collings et al, 2011;Walts, 2012). Findings showed that women who were appointed to administrative positions in the academic workplace need support from other professional administrators in their department to adjust to their profession and to recognize the structure of the department (Beck, 2008).…”
Section: Organizational Practicesmentioning
confidence: 99%
“…Demonstrating effective leadership in Higher Education (HE) in the UK has become of increasing importance in recent years, particularly with changes in the HE sector that are making more demands of senior leaders and an increased emphasis on the professionalism of academic staff ( [1], [3], [4]). However, often universities are ill-equipped from a leadership development perspective to meet these challenges.…”
Section: Introductionmentioning
confidence: 99%